Best Answer

3 X 2 + 10 - 3 ( 8 - 6 )

3 X 2 + 10 - 3 ( 2 ) Parentheses first

6 + 10 - 6 There are no exponents, so multiplication and division next

10 Addition and subtraction last

Q: What is 3 times 2 plus 10 minus 3 and in parentheses 8 minus 6 in pemdas?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

parentheses two times nine parentheses times negative eight minutes four parentheses four plus hundred plus eight

+ times a + = a plus- times a + = a minus- times a - = a plus+ times a - = a minus

plus times plus = plus minus times plus = minus plus times minus = minus minus times minus = plus so when you subtract a number it is the same as adding its negative; for example 7 - 4 = 3 7 + (1)(-4) = 3

A plus times a plus is still a plus. Below is the way I remembered it: If there is not a minus sign, it is plus (positive). If there is 1 minus sign, it is minus (negative). If there are 2 minus signs, it is plus (positive).

As written, those are the same. For that sentence to equal 3, we need to use parentheses. (8 + 4) divided by 2 minus (1 x 3)

Related questions

It is 5.

(43 - 19) + (16 - 14)(4)= 24 + (2)(4)= 24 + 8= 32

Just take the parenthesis and you will have your answer.

parentheses two times nine parentheses times negative eight minutes four parentheses four plus hundred plus eight

54 - (6 / 2) + 6 54 - 3 + 6 51 + 6 57 Remember, PEMDAS: Parentheses, Exponents, Multiplication and Division, Addition and Subtraction.

1316 - ( 1416 + 316 ) = - 416

-2w+14+10w=348w=20w=2.5

+ times a + = a plus- times a + = a minus- times a - = a plus+ times a - = a minus

assuming that there are no parentheses around the (7-1) then it should be 10.7

2 * 70 - 9 / 3 + 8= 140 - 3 + 8= 140 - 11= 129

-20 Yes, that's correct. This is what it means:- 2(-3-5)-(2 + 2) And that is 2 x (-3-5) - (2 +2) = 2 x (-8) -(4) = -16 - 4 = -20

plus times plus = plus minus times plus = minus plus times minus = minus minus times minus = plus so when you subtract a number it is the same as adding its negative; for example 7 - 4 = 3 7 + (1)(-4) = 3